Problem-Based Learning Model Assisted by Mind Mapping to Enhance Elementary Students’ Critical Thinking in Science Viewed from Self-Efficacy - Ni Nyoman Sri Arianti; I Made Citra Wibawa; Ketut Suma (Journal of Education Reseach and Evaluation, 2026)
The low level of students’ critical thinking skills in science learning is primarily attributed to instructional practices that are still dominated by basic question-and-answer methods and limited discussions. This study aimed to analyze the effect of the Problem Based Learning (PBL) model assisted by mind mapping on elementary school students’ science critical thinking skills in terms of their self-efficacy. This research employed a quantitative approach using a quasi-experimental design. The population consisted of 324 fourth-grade elementary school students, and random sampling was used to select the research sample. Data were collected through questionnaires and essay tests, with self-efficacy and critical thinking tests serving as the research instruments. Data analysis techniques included descriptive analysis and analysis of covariance (ANCOVA). The results indicated that: first, there were significant differences in science critical thinking skills between students taught using the PBL model assisted by mind mapping and those taught using conventional learning models. Second, there was a significant interaction effect between the PBL model assisted by mind mapping and students’ self-efficacy on science critical thinking skills. Third, there were significant differences in science critical thinking skills between students with high self-efficacy who learned through the PBL model assisted by mind mapping and those who learned through conventional models.Fourth, there were significant differences in science critical thinking skills between students with low self-efficacy who learned through the PBL model assisted by mind mapping and those who learned through conventional models.